162k views
3 votes
Given f(x) = 4x + 13 and g(x) = 10x − 2, solve for (f + g)(x) and select the correct answer below. (f + g)(x) = 14x + 15 (f + g)(x) = 14x + 11 (f + g)(x) = 6x + 11 (f + g)(x) = 6x + 15

2 Answers

2 votes

Answer:

B

Explanation:

trust me

User Unlink
by
5.1k points
2 votes
Actually, we're combining two separate functions into one, not solving anything.

f(x) = 4x + 13 and g(x) = 10x − 2 should be written one above the other:

f(x) = 4x + 13 and
g(x) = 10x − 2

Now add like terms together:

(f+g)(x) = 14x + 11 (answer)
User Mark Thistle
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.